An Opioid Sparing Anesthesia Protocol for Pediatric Open Inguinal Hernia Repair: A Quality Improvement Project. Issue 2 (March 2022) - Chiem, Jennifer L.; Franz, Amber; Bishop, Nicholas; Liston, David; Low, Daniel K.
Abstract : Introduction: Using plan-do-study-act (PDSA) cycles, this quality improvement (QI) project aimed to standardize an anesthetic protocol to optimize multimodal pain management for pediatric open inguinal hernia repair (OIHR). Methods: PDSA cycle 1: in December 2017, we standardized the intraoperative OIHR anesthesia protocol by replacing transversus abdominis plane (TAP) or ilioinguinal-iliohypogastric (II) blocks and fentanyl with exclusively II blocks and fentanyl. PDSA cycle 2: in January 2019, we used an opioid sparing strategy, replacing II blocks and fentanyl with II blocks and dexmedetomidine. We used statistical process control (SPC) charts to analyze data from the medical record. Outcome measures included the percent of patients requiring rescue morphine in the postanesthesia care unit (PACU), maximum PACU pain score, PACU length of stay (LOS), and anesthesia preparation duration. Results: The team performed a total of 641 pediatric OIHRs between July 2015 and June 2021. The three groups included 203 patients in our baseline group, 127 patients in the PDSA cycle 1 group, and 311 patients in the PDSA cycle 2 group. Special cause variation (SCV) occurred for the percent of patients requiring rescue morphine, anesthesia preparation duration, and PACU LOS. The percent of patients requiring rescue morphine showed improvement. Anesthesia preparation duration improved compared to baseline. There was no SCV detected in the SPC chart for maximum PACU pain score. Conclusion: We implemented an opioid sparing anesthetic protocol for pediatric OIHR utilizing II blocks and dexmedetomidine without adversely affecting postoperative pain score or morphine rescue rate over 6 years.